2018
DOI: 10.1021/acs.joc.8b01390
|View full text |Cite
|
Sign up to set email alerts
|

Application of Naphthylindole-Derived Phosphines as Organocatalysts in [4 + 1] Cyclizations of o-Quinone Methides with Morita–Baylis–Hillman Carbonates

Abstract: An organocatalytic [4 + 1] cyclization of o-QMs with MBH carbonates has been established using naphthylindole-derived phosphine (NIP) as an organocatalyst. By using this approach, a series of 2,3-dihydrobenzofuran derivatives have been synthesized in high yields and excellent diastereoselectivities (up to 99% yield, >95:5 dr). This reaction not only has established the first [4 + 1] cyclization of o-QMs with MBH carbonates but also represents the first application of naphthylindole-derived phosphines as organo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…More importantly, compound 12 aa was transformed into chiral phosphine 14 by reduction of compound 13 . Notably, phosphine 14 with both axial and central chirality was utilized as a new chiral organocatalyst to promote the catalytic asymmetric [4+1] cyclization of o ‐QM 15 with Morita–Baylis–Hillman carbonate 16 to generate product 17 in good enantioselectivity (Scheme g) . This result demonstrated that this class of naphthyl‐indole‐derived phosphines can be developed as a new type of chiral organocatalyst.…”
Section: Resultsmentioning
confidence: 93%
“…More importantly, compound 12 aa was transformed into chiral phosphine 14 by reduction of compound 13 . Notably, phosphine 14 with both axial and central chirality was utilized as a new chiral organocatalyst to promote the catalytic asymmetric [4+1] cyclization of o ‐QM 15 with Morita–Baylis–Hillman carbonate 16 to generate product 17 in good enantioselectivity (Scheme g) . This result demonstrated that this class of naphthyl‐indole‐derived phosphines can be developed as a new type of chiral organocatalyst.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, Zhang and co‐workers devised an enantioselective (4 + 1) annulation of MBH carbonates with ortho ‐quinone methides 66 catalyzed by a newly designed chiral phosphine 68 , delivering a wide range of polysubstituted dihydrobenzofurans 67 in good yields with high diastereoselectivity and excellent enantioselectivities (Scheme , top) . Moreover, the Shi group also reported a similar (4 + 1) annulation with ortho ‐quinone methides 66 using a novel naphthylindole‐derived phosphine catalyst 70 , which allowed the formation of 2,3‐dihydrobenzofuran derivatives 69 bearing two vinyl moieties in high yields and excellent diastereoselectivity (Scheme , bottom) …”
Section: (4 + 1) Annulation Reactions Of Morita–baylis–hillman (Mbmentioning
confidence: 99%
“…Shi and co-workers (2018) reported the reaction of substituted 4,5-(methylenedioxy)-o-quinone methides with Morita-Baylis-Hillman carbonates using naphthylindolederived phosphine B as organocatalyst to give a series of DHB derivatives in up to 92% yield and >95:5 dr (Scheme 9). 40 Li, Li, and co-workers (2018) reported the use of 1,2bis[(2R,5R)-2,5-dimethylphospholano]benzene monoxide C as a catalyst for the reaction of stabilized o-quinone methides with Morita-Baylis-Hillman carbonates to give a series of optically active DHBs in 23-67% yields and with 87-94% ee and >20:1 dr (Scheme 9). 41 By using (-)-1,2bis[(2R,5R)-2,5-dimethylphospholano]benzene D as the catalyst in this reaction, the desired chiral DHBs were obtained in 42-90% yields and with 76-87% ee and >20:1 dr (Scheme 9).…”
Section: Scheme 9 Dhbs From Stabilized O-quinone Methidesmentioning
confidence: 99%